The History of Canon Law as a Proper Mirror to Deepen Current Legal Conflicts - Domenico Bilotti (Religions)
It is important to underline that the history of Canon Law has a specific significance, even considering the methodological opportunity to find and to reconsider documents, periods, and personalities in order to modify and to enhance already acquired hermeneutical data. A partially unexplored hypothesis, however, consists in the peculiar attitude of Canon Law in approaching themes coming from the current configuration of legal relationships because the ecclesial paradigm has represented a primary framework, not only in Western societies, for Christian cultures and a not necessarily hostile and antithetical model to the others. By selecting a restrained amount of critical case studies, this essay will consider juridical institutes related to the legitimacy of public authorities, the legal protection of dissent (but on the basis of limited circumstances), the Private law possibility to realize human interests in a pacific, mutual, contractual way.